The Role Of Frequently Used Clinical And Laboratory Findings In The Differential Diagnosis Of Acute Appendicitis And Ruptured Ovarian Cyst (Annals of Medical Research, 2021)
None
Keywords: s : Acute appendicitis, ovarian cyst, differential diagnosis